ANALISIS NILAI KAKAWIN RATNA PAUKIRAN - Pravasta Priyastini, Ni Kadek Mirah (Humanis; Volume 11. No2. Mei 2015, 2015)
Kakawin Ratna Paukiran is one kakawin minor. Kakawin Ratna Paukiran tells of a beautiful princess and a major all-around beauty who likes to be at sea and in the mountains. The princess craze surrounding mountains, it is also called the mountain girl. Inside there Paukiran Ratna Kakawin life values that need to be disclosed in order to determine the values of what is contained in it. This study resulted in the analysis of value Kakawin Ratna Paukiran include: religious values, ethical values, educational values, and the value of heroism.
Keywords: Kakawin, Ratna Paukiran, and value